IFRS: A Conceptual Understanding and Framework - Kaur, Jasmine (Indian Journal of Finance, 2011)
The International Financial Reporting Standards are to be implemented in India from 1/04/2011. And, still, there are many unanswered questions w.r.t its conceptual framework, implementation, impact and other related issues. Answers to these questions will definitely help to increase our knowledge leading to better analysis. In this paper, an effort has been made to get a conceptual understanding of IFRS and its framework in the Indian context. It was realized that there are certain significant differences between International Financial Reporting Standards and Generally Accepted Accounting Principles. Also, there would be a major impact on the key industries and certain challenges to be faced while adopting IFRS but the benefits definitely outweigh the disadvantages.